Praktik Pengembangan Program Perhutanan Sosial Sebagai Strategi Pelestarian Kawasan Hutan di Desa Yehembang Kangin - Farkha Alfa Centauri; Tahsa Ayu Seva; Galang Alhaya Dinasti; Hendra Bagus Pamungkas (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Along with the pace of development and economic growth in a region, it cannot be separated from various kinds of activities that are at risk of environmental destruction, one of which is forests. Where, this has concretely occurred in the increasing cases of encroachment on forest areas in Jembrana Regency. This encroachment was triggered by "ngawen" activities and illegal logging which caused environmental damage and loss of biodiversity. Here, PT Pertamina Patra Niaga Aviation Fuel Terminal (AFT) Ngurah Rai plays a role in assisting the development of social forestry programs in Yehembang Kangin Village, Mendoyo District, Jembrana Regency, Bali Province to be able to increase public awareness of the importance of protecting forests and empowering the communities who are members of it. Banu Giri Lestari Forest Farmers Group in a sustainable manner. This research uses a descriptive qualitative approach supported by data collection techniques using purposive sampling. The results of the research show that the social forestry development program in Yehembang Kangin Village provides positive changes for the transformation of group behavior in forest conservation. Producing local heroes and their regeneration who are expected to be able to become agents of change in managing forests wisely and responsibly. Apart from that, the group has also been able to take the initiative in cultivating wood and fruit forest plants independently by practicing the "tanem tuwuh" pattern to support ecosystem sustainability and increase the diversity of flora and fauna in the forest.